2021
DOI: 10.1108/hff-03-2021-0172
|View full text |Cite
|
Sign up to set email alerts
|

Entropy generation in MHD free convection of nanoliquid within a square open chamber with a solid body

Abstract: Purpose The study aims to investigate magnetohydrodynamics thermal convection energy transference and entropy production in an open chamber saturated with ferrofluid having an isothermal solid block. Design/methodology/approach Analysis of thermal convection phenomenon was performed for an open chamber saturated with a nanofluid having an isothermal solid unit placed inside the cavity with various aspect ratios. The left border temperature is kept at Tc. An external cooled nanofluid of fixed temperature Tc p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
(114 reference statements)
0
3
0
Order By: Relevance
“…Their study revealed that increasing the magnetic field values leads to a reduction in the Bejan number. Chinnasamy et al (2021) used the finite volume method to numerically examine entropy generation in an open cavity filled with a water-based nanofluid containing ferric oxide nanoparticles. The study revealed that a decrease in temperature drop leads to a reduction in the average entropy generation due to the altered energy transport.…”
Section: Keller Box Computationmentioning
confidence: 99%
“…Their study revealed that increasing the magnetic field values leads to a reduction in the Bejan number. Chinnasamy et al (2021) used the finite volume method to numerically examine entropy generation in an open cavity filled with a water-based nanofluid containing ferric oxide nanoparticles. The study revealed that a decrease in temperature drop leads to a reduction in the average entropy generation due to the altered energy transport.…”
Section: Keller Box Computationmentioning
confidence: 99%
“…The stabilizing impacts of exerted magnetic field were also deliberated in Zaydan et al (2020) on the Buongiorno’s nanofluid model convection. More results of Lorentz force on fluid flow phenomena can be referred to the recent works (Shehzad et al , 2021; Chinnasamy et al , 2021; Dutta et al , 2022; Manna et al , 2023).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, when the magnetic field angle is 30 ∘ , the total irreversibility is at its minimum value. MHD thermal convection and entropy generation in an open cavity with saturated ferro nanofluid were studied by Chinnasamy et al (2021). A uniform magnetic field was applied to the cavity with an inner isothermal solid.…”
Section: Introductionmentioning
confidence: 99%